The load-transfer method as a tool for determining the load-displacement curve of piles - Chalmovský, Juraj; Račanský, Václav; Koudela, Pavel; Zdražil, Karel (CZECH TECHNICAL UNIV PRAGUE, 2024)
The paper presents two applications (software packages) in which the load-transfer method is used for axially loaded Kelly drilled bored piles and displacement ductile iron piles. In the first, the ultimate friction is related to the effective stress via the so-called beta method. The beta method is refined into three stages to cover the variety of soils typical of Central Europe. For the driven piles, a different approach is presented in which the ultimate shaft friction is related to the reference hammering time. The recorded hammering time profile is fed directly into the software based on the load-transfer method. Analyses of five loading tests are presented proving that the load transfer method in combination with the beta method or the recorded hammering time profile is able to compute the load-displacement curve of both replacement and displacement piles with a reasonable accuracy in various geological conditions.

The paper presents two applications (software packages) in which the load-transfer method is used for axially loaded Kelly drilled bored piles and displacement ductile iron piles. In the first, the ultimate friction is related to the effective stress via the so-called beta method. The beta method is refined into three stages to cover the variety of soils typical of Central Europe. For the driven piles, a different approach is presented in which the ultimate shaft friction is related to the reference hammering time. The recorded hammering time profile is fed directly into the software based on the load-transfer method. Analyses of five loading tests are presented proving that the load transfer method in combination with the beta method or the recorded hammering time profile is able to compute the load-displacement curve of both replacement and displacement piles with a reasonable accuracy in various geological conditions.
The load-transfer method as a tool for determining the load-displacement curve of piles
Keywords: Load-transfer method; deep foundations; pile; ultimate shaft friction; base resistance; load-displacement curve; effective stress; Load-transfer method; deep foundations; pile; ultimate shaft friction; base resistance; load-displacement curve; effective stress